2020
DOI: 10.1111/nicc.12582
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family involvement in escalating concerns about clinical deterioration in acute adult wards: A qualitative systematic review

Abstract: Background Despite international standards for recognition and response to deterioration, warning signs are not always identified by staff on acute hospital wards. Patient and family‐initiated escalation of care schemes have shown some benefit in assisting early recognition, but are not widely used in many clinical practice areas. Objectives To explore (a) patients' and relatives' experiences of acute deterioration and (b) patients', relatives' and healthcare professionals' perceptions of the barriers or facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…Lastly, our findings have shown that whilst patients and their relatives can act to scaffold the clinical system, it is imperative that the system is designed to take account of patient concerns. As McKinney and colleagues (2021) note, changes in ward culture are needed to truly hear the patient. Healthcare professionals require organisational support in order to create an environment where compassionate care is prioritised ( Crawford et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our findings have shown that whilst patients and their relatives can act to scaffold the clinical system, it is imperative that the system is designed to take account of patient concerns. As McKinney and colleagues (2021) note, changes in ward culture are needed to truly hear the patient. Healthcare professionals require organisational support in order to create an environment where compassionate care is prioritised ( Crawford et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Albutt and colleagues explored the use of a method to capture patient-led identification of deterioration and found that patients were willing and able to report information about how well they felt during routine observations ( Albutt et al, 2020 ). McKinney and colleagues (2021) conducted a qualitative systematic review of patient and family involvement in escalating concerns about clinical deterioration. They found that any involvement depended on the capacity and capability of patients to identify deterioration, as many patients were unable to discern a change in their clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Factors have been identified that act as both barriers and facilitators to being heard, including personal factors (such as previous experience or knowledge of illness) and personality traits determining how confident patients and families will feel about responding to changes and raising concerns. 27 Perceptions of the patient-healthcare professional's role, including the notion that the healthcare professional 'knows best', also contribute to a reluctance to voice concerns and to the adoption of a passive role. In addition, the quality of relationships between patients/families and healthcare professionals can promote or inhibit the ability to speak up.…”
Section: Opportunities and Barriers For Implementation Of Patient And Family Activated Rapid Responsementioning
confidence: 99%
“…28 Given these challenges, there is a need to further consider the processes and interventions that will influence patient and relative empowerment in this area and help patients and families to move more confidently towards feeling that they have 'permission to participate'. 27,29 Systematic review evidence recommended that, given the paucity of robust research in this area, further research was required that utilised a structured approach and included consumer involvement in the development of an escalation of care intervention. 30,31 To further explore these and other contextual factors that may impact on their role, and to address some of the identified challenges, a Health Service Executive funded project in Belfast co-designed a patient and family escalation of care prototype resource based on the experiences of patients, relatives and healthcare professionals to improve patient and family engagement across Ireland.…”
Section: Opportunities and Barriers For Implementation Of Patient And Family Activated Rapid Responsementioning
confidence: 99%
“…Nurses' competence in recording and interpreting patient observations in acute care settings has also been the subject of review 10 and innovation to improve staff detection and response to acute illness 11 . The contribution of patient and family involvement in escalating concerns about clinical deterioration in acute wards was the focus of a qualitative systematic review by McKinney et al 12 Five studies were identified as eligible for inclusion and subjected to quality appraisal. The population in the review represented the experiences of patients and relatives, mainly recruited from acute medical and surgical wards.…”
mentioning
confidence: 99%